Censorship and Digital Games Localisation in China - Zhang, Xiaochun (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2012)
Censorship and translation is a topic that has received substantial attention in academic circles in recent years. Although much of the research has focused on the interrelationship between these two areas, censorship systems and their influence on audiovisual translation, especially digital games localisation, has not been fully examined within the scope of translation studies. This article aims to fill that gap by investigating censorial operations on digital games against the socio-cultural background of Mainland China. It will provide an overview of the Chinese censorship system, with a particular focus on the censoring authorities, their reviewing procedures and methods, including the regulations and standards on game content. It questions the extent to which censorship influences games localisation in practice and concludes that game localisers tend to perform stringent self-censorship when the censorship system itself lacks transparency.